Innovative Approaches in Early Childhood Education: Enhancing Receptive Language Skills Through Interactive Audiovisual Media - Muhammad Dhani Fauzan Sajid; Rozman Ab. Kadir; Heleni Filtri (Universitas Lancang Kuning, 2024)
This research is an R&D research which aims (1) to find out the description of the need for using audio-visual based learning media in improving Receptive Language skills in children (2) To find out the development of audio-visual based learning media in improving Receptive Language skills in children (3) To Knowing the validity, practicality and effectiveness of audio-visual based learning media in improving Receptive Language skills in children. This research design uses a 4-D model. Data collection techniques in this research were observation and questionnaires. The subjects in this research consisted of 3 teachers and 14 students. The results of the research show that: (1) an overview of the need for developing audio-visual based learning media in improving children's receptive language skills, which is really needed by teachers because audio-visual based learning media is considered very practical in improving children's receptive language skills, 2) Learning development plans The audio-visual-based design was designed, namely: Media and a guidebook for using the media, and 3) the level of validity of audio-visual-based learning media obtained an average result from two validators ini very valid category, and the level of practicality based on the teacher response questionnaire with very practical criteria. Meanwhile, in the effectiveness test of the media evaluation sheet questionnaire with very effective. criteria and analysis of the children's data obtained shows that H1 is accepted and H0 is rejected, so it is said that there is an influence of audio-visual media on children's receptive language.